PERAN GURU PAK SEBAGAI AGEN TRANSFORMASI NILAI KRISTIANI DALAM PEMBENTUKAN KARAKTER DISEKOLAH PADA ERA PERUBAHAN ZAMAN - Stefany Londonaung; Abida Masosendifu; Wilsa Wakris; Jeanet Mandagie; Nurhalisa Pangisian; Ayu Kirimang; Nata Tabuni; Leanscy Sucea Lengkoan; Lumius Wenda (MATA GURU: Jurnal Pendidik dan Tenaga Kependidikan, 2026)
This article discusses the important role of Christian Religious Education (PAK) teachers as agents of change who are grounded in Christian values amid the dynamics of modern times. Christian values have a significant influence on students' lives, especially in today’s era, which demands that they adapt to rapid developments and changes. This study employs a literature review method by examining various sources such as books, scholarly journals, and articles. The purpose of this research is to explore the role of PAK teachers as transformational agents who help shape students’ character so that they remain rooted in Christian values as a foundation for facing change